Analysis of insertions and extensions in the functional evolution of the ribonucleotide reductase family. (17th November 2022) - Burnim, Audrey A.; Xu, Da; Spence, Matthew A.; Jackson, Colin J.; Ando, Nozomi
Abstract: Ribonucleotide reductases (RNRs) are used by all free‐living organisms and many viruses to catalyze an essential step in the de novo biosynthesis of DNA precursors. RNRs are remarkably diverse by primary sequence and cofactor requirement, while sharing a conserved fold and radical‐based mechanism for nucleotide reduction. In this work, we expand on our recent phylogenetic inference of the entire RNR family and describe the evolutionarily relatedness of insertions and extensions around the structurally homologous catalytic barrel. Using evo‐velocity and sequence similarity network (SSN) analyses, we show that the N‐terminal regulatory motif known as the ATP‐cone domain was likely inherited from an ancestral RNR. By combining SSN analysis with AlphaFold2 predictions, we also show that the C‐terminal extensions of class II RNRs can contain folded domains that share homology with an Fe‐S cluster assembly protein. Finally, using sequence analysis and AlphaFold2, we show that the sequence motif of a catalytically essential insertion known as the finger loop is tightly coupled to the catalytic mechanism. Based on these results, we propose an evolutionary model for the diversification of the RNR family.